Harvested rainwater quality assessment on the effects of roof materials to the first flush runoff - Janice Lynn Ayog (e-VIBS, Faculty of Science and Natural Resources, 2016)
This study focuses on the effects on roofing materials on the first flush runoff quality. An experimental rainwater harvesting system was designed and built on the compound of the Civil Engineering Hydraulic Laboratory, Universiti Malaysia Sabah, to assess the effects of two different types of roofs - locally-sourced nipah-thatched roof and galvanized iron roof – on the quality of the harvested rainwater in the university. The first flush runoff from the rainwater collected on the 8th June 2015 was analysed for four water quality parameters, namely pH, total suspended solids (TSS), turbidity and dissolved oxygen (DO). The results obtained from this study were then checked to the water quality threshold limit of the Interim National Water Quality Standards for Malaysia (INWQS) and compared to selected previous studies. It is found that the first flush runoff quality for the nipah-thatched and the galvanized iron roofs were relatively good, except for turbidity (nipah-thatched roof only) and DO. The pH concentration levels from this study is in neutral range (5-7) as most previous researches, but the TSS concentration levels were relatively lower. The turbidity and DO levels of the galvanized iron roof were quite similar with other roofs, however the nipah-thatched roof had higher concentration levels as compared to the previous studies. As the water quality results could be influenced by the roof age, further investigation will be done on this factor to the harvested rainwater quality.